Economie dell'incertezza: festa, località, autonomia simbolica. Una nota - Francesco Faeta (EtnoAntropologia)
Data on a case study are outlined in this note, through general and indicative lines. By the way of this case study, one can see the existence of an economic and social field, related to the shortage of resources and to the lack of concrete expectations of the future, which sees massively (though not exclusively) protagonists the younger generation. At the very center of this field there are the feast, the rite and the connected emphasis on local identities. This delineates autonomy, when not a real independence, of the symbolic components from the structural plane, their establishment as a fundamental element of economic and social organization (above all, but not only, with regard to tourism and to the relationship between local community and global reality). The case study focuses on an emblematic region of national underdevelopment, Calabria, but what is happening there is certainly significant to wider realities.